Sistem Informasi Peserta Paket C Pada Pusat Kegiatan Belajar Masyarakat (PKBM) Cakrawala Kabupaten Kepahiang - Deri Novrian; Asnawati Asnawati; Ricky Zulfiandry (Jurnal Media Infotama, 2025)
Making information systems for “Paket C” participants is an urgent need for PKBM in order to improve the quality and effectiveness of non-formal education services. Based on these conditions the researcher tries to design a sales information system that is in accordance with the problems that have been analyzed, to produce an information system design that can help the next programmer create an application program in order to produce higher quality information, the programming language that the researcher plans is to use a web program which is expected to help work in data processing to be more effective and efficient. The analysis carried out is: context diagram, relationship between files, database design, menu and sub menu design, input design, output design, using the waterfall method. PKBM (Community Learning Center) Information System has enormous potential in improving the quality of non-formal education management, especially for Paket program. The implementation of this system can speed up the administrative process, facilitate the management of student data, and provide convenience in making reports that are more accurate and timely, With an integrated system, PKBM can monitor the development of students more efficiently, starting from registration, attendance, test scores, to graduation, To achieve optimal results, the implementation of this information system requires serious attention to several supporting factors, such as adequate infrastructure, training for managers and system users, and readiness to face technological challenges.